ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODIKTIVITAS TENAGA KERJA PEMANEN KELAPA SAWIT PADA PT. BUANA ESTATE DI KECAMATAN SECANGGANG KABUPATEN LANGKAT SUMATERA UTARA - Lestari, Sindi Indah; Mahyuddin, Thursina; Basriwijaya, Kiagus Muhammad Zain; Anzitha, Silvia; Gustiana, Cut (Universitas Medan Area, 2024)
Palm oil is one of the plantation-produced commodities which has quite an important role in economic activities in Indonesia because of its ability to produce vegetable oil which is much needed by the industrial sector. This research discusses the impact of the agricultural sector, especially palm oil production at PT. Buana Estate, Secanggang District, Langkat Regency, North Sumatra, towards the national economy, with a focus on analyzing the factors that influence the productivity of oil palm harvesters. The aim of this research is to analyze the influence of salary, experience, age and harvest premium on the productivity of oil palm harvesters at PT. Buana Estate in Secanggang District, Langkat Regency, North Sumatra. This research was carried out from January to February 2023. This research used a sampling method using the case study method. The sample used in this research was 30 respondents. The sample in this research was oil palm harvesting employees. Based on the research results obtained from the t test results on the salary level and harvest premium variables which influence labor productivity, this can be seen from the salary significance value of 0.000 and the harvest premium significance value of 0.000. The work experience and age variables have no effect on labor productivity, this can be seen from the work experience significance value of 0.133 and the age significance value of 0.275. These results indicate that efforts to increase salaries and provide more effective harvest premiums can be a strategy to increase the productivity of oil palm harvesters at PT. Buana Estate. This research contributes to the context of sustainable development in the palm oil plantation sector and provides practical insights for companies in improving worker welfare and productivity.